MENUNGGU KIPRAH NEGARA PADA SEKOLAH RUMAHAN ALA SAMIN: Studi Kasus di Kudus - Moh Rosyid (usat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2021)
This research was conducted to understand the home school model of Samin residents in Kudus, Central Java. Research data obtained through interviews, observations, and literature review. Data was analyzed using a qualitative descriptive approach. Samin’s home school was initially led by Ki Samin Surosentiko during the resistance against the Dutch colonial in Blora and has spread to Kudus until now. Samin residents do not go to formal schools, but form home schools with the aim of protecting their generation from being carried away by the current dynamics. The learning materials focus on the principles of life and to stay away from five taboos: bedok (accusing), colong (stealing), pethil; pinch; and nemu wae ora keno; taboo to find goods. Samin residents do not go to formal schools because they still maintain their ancestral teachings with speech traditions. The educators are parents and traditional leaders. The results of the evaluation are reflected in their behavior in life. The Samin people’s passions are to serve, care for, and protect Ki Samin’s teachings in terms of ordinances, manners, and dharma so that the roots of the noble tradition are maintained. The success of homeschooling is reflected when students behave according to the teachings of their parents and can be followed as examples. The state must be present to provide continuous enlightenment so that its curriculum leads to formal education or equality, while also maintaining that local wisdom is not uprooted from its cultural roots. The role of the state ideally is to explicate with a persuasive approach, so that the teaching material could integrate formal homeschooling. Penelitian ini dilakukan untuk memahami model sekolah rumahan warga Samin di Kudus Jawa Tengah. Data riset diperoleh melalui wawancara, observasi, dan kajian pustaka. Analisis data menggunakan pendekatan deskriptif kualitatif. Sekolah rumahan Samin awalnya dimotori oleh Ki Samin Surosentiko di masa perlawanan kolonial Belanda di Blora dan menyebar sampai Kudus hingga kini. Warga Samin tidak bersekolah formal, tetapi membentuk sekolah rumahan dengan tujuan memproteksi generasinya agar tidak terbawa dinamika kekinian. Materi pembelajarannya berfokus pada prinsip hidup dan menjauhi lima pantangan: bedok (menuduh), colong (mencuri), pethil; jumput; dan nemu wae ora keno; pantangan menemukan barang. Warga Samin tidak bersekolah formal karena masih mempertahankan ajaran leluhur dengan tradisi tutur. Pendidiknya adalah orang tua dan tokoh adat. Hasil evaluasi tercermin pada perilaku hidupnya. Obsesi orang Samin yaitu nglayani, ngrawat, nglindungi ajaran Ki Samin dalam hal tata cara, tata krama, dan tata darma agar akar tradisi adiluhung terawat. Keberhasilan sekolah rumahan tercermin ketika peserta didik berperilaku sebagaimana ajaran orang tua dan dapat diteladani. Negara harus hadir memberi pencerahan secara berkesinambungan agar kurikulumnya mengarah pada pendidikan formal atau kesetaraan dan kearifan lokalnya tak tercerabut dari akar budayanya. Peran negara idealnya menjelaskan agar materi ajarnya menjadi homeschooling formal dengan pendekatan persuasif.